The dictionary story - Jeffers, Oliver; Winston, Sam (Somerville, Massachusetts : Candlewick Press, 2024)
Dictionary wishes she could tell a story like other books. So one day, she decides to bring her words to life. How exciting it is to finally have an adventure on her very own pages! But what will she do when her characters collide and everything gets all in a jumble, causing the most enormous tantrum to explode? This isn't what she wanted at all! Luckily her friend Alphabet knows exactly what to do and sings a song that brings calm and order to Dictionary's pages once again.
Letter "A" is crossed out and replaced with "The" in the title.
Booklist starred, June 2024
Publishers Weekly, April 2024
Kirkus Starred, June 2024
K-3
Keywords: Encyclopedias and dictionaries -- Juvenile fiction; Vocabulary -- Juvenile fiction; Books and reading -- Juvenile fiction; Humorous stories; Encyclopedias and dictionaries -- Fiction; Vocabulary -- Fiction; Books and reading -- Fiction; Humorous fiction